Digital competence and digital entrepreneurial intention: A social cognitive approach - Bao Quoc Lam; Hao Yen Tran; Kiet Anh Nguyen; Kiet Tuan Nguyen; Minh Pham (Entrepreneurial Business and Economics Review)
Objective: This article aims to investigate how digital competence moderates the relationship between entrepreneurial education and digital entrepreneurship intention among university students within the framework of social cognitive career theory.